2021
DOI: 10.1155/2021/6074039
|View full text |Cite
|
Sign up to set email alerts
|

Learner Autonomy in L2 Writing: The Role of Academic Self-Concept and Academic Achievement

Abstract: Embracing a learner-based approach in line with a psychological perspective, the present study investigates learner autonomy (LA) in L2 writing with a focus on the role of academic self-concept (ASC) and academic achievement of Iranian English-as-a-Foreign-Language (EFL) university students. The research entailed three interrelated phases: In phase one, the readiness of 69 EFL students in three intact English essay writing classes was measured in terms of certain factors of autonomy in writing. Besides, their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It is proposed that teachers should provide and trigger learners with relevant topics. Some other reasons related to writing anxiety are academic self-concept [ASC] and academic achievement (Tajmirriahi & Rezvani, 2021). Academic self-concept and academic achievement from the learners affect their motivation in writing.…”
Section: Writing Skillmentioning
confidence: 99%
“…It is proposed that teachers should provide and trigger learners with relevant topics. Some other reasons related to writing anxiety are academic self-concept [ASC] and academic achievement (Tajmirriahi & Rezvani, 2021). Academic self-concept and academic achievement from the learners affect their motivation in writing.…”
Section: Writing Skillmentioning
confidence: 99%
“…Students' complete exercises from the textbook in the classroom and at home, most of which are traditionally performed by International Journal of English Language and Literature Studies tracking. However, Tajmirriahi and Ehsan (2021) examined learner readiness in L2 writing to explore any potential linkages between LA in writing, academic self-concept (ASC), and academic accomplishment. The results revealed that while participants showed positive attitudes towards LA writing practices to some extent, they were not completely ready to employ those practice strategies in such contexts.…”
Section: Introductionmentioning
confidence: 99%